2019
DOI: 10.16984/saufenbilder.540294
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Symmetrical and Unsymmetrical Short Circuit Fault Analyses in Power Systems

Abstract: In this study, the common symmetrical and unsymmetrical short circuit faults in power systems are analyzed detailed. Unlike the similar studies in the literature, metallic fault conditions for unsymmetrical faults are also given in the paper additionally. For this aim, a short circuit analysis algorithm is created for the analysis of both three phase short circuit, line-to-line short circuit with fault impedance, metallic line-to-line short circuit, double line-to-ground short circuit with fault impedance, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Line to Line fault is a short circuit condition between any two phases of a system. L-L faults are the second most common minor distribution system faults, with a percentage of 8%-10% [7], [25], [26]. Lineto-line (L-L) fault in a three-phase power system can be expressed in phasor form as follows:…”
Section: Asymmetrical Faultmentioning
confidence: 99%
“…Line to Line fault is a short circuit condition between any two phases of a system. L-L faults are the second most common minor distribution system faults, with a percentage of 8%-10% [7], [25], [26]. Lineto-line (L-L) fault in a three-phase power system can be expressed in phasor form as follows:…”
Section: Asymmetrical Faultmentioning
confidence: 99%
“…When a short circuit occurs, the all considered internal impedance replaces components and an equivalent voltage source is implemented at the fault node the equivalent short-circuits impedance of the system electrical system. Faults are generally divided into two broad categories in today's power systems [19];  Symmetrical or balanced faults (three phase)  Asymmetrical or unbalanced faults.…”
Section: Short Circuit Analysismentioning
confidence: 99%
“…In the literature, there are many studies that showed the changes in current and voltage during short circuit which bases on the basis of power system design. Some authors used for demonstrating fault simulation studies and analyses on the IEEE-9 bus [16][17][18], IEEE-14 bus [19] and 39-bus New England System [18], while other authors examined modeled real data based on which are substation in Turkey [20], substation in India [21], wind power plant [17], nuclear power plant [22]. There are many software in the literature that are widely used to perform short circuit analysis, which are Matlab [16,19,20,23], PSCAD [24], Power World Simulator [25,26], ETAP [17,18,21,27] and DigSilent [22,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DLG through metallic or a fault impedance are unsymmetrical or unbalanced faults that create severe unbalanced operating conditions. The SLG and DLG faults can be analyzed into three symmetrical components which are three balanced sets (positive, negative, and zero circuits) [8,9].…”
mentioning
confidence: 99%